2021
DOI: 10.1289/ehp7352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Dose Gestational TCDD Exposure on Behavior and on Hippocampal Neuron Morphology and Gene Expression in Mice

Abstract: BACKGROUND: 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) is a persistent and toxic environmental pollutant. Gestational exposure to TCDD has been linked to cognitive and motor deficits, and increased incidence of autism spectrum disorder (ASD) traits in children. Most animal studies of these neurodevelopmental effects involve acute TCDD exposure, which does not model typical exposure in humans. OBJECTIVES: The aim of the study was to establish a dietary low-dose gestational TCDD exposure protocol and performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 143 publications
(194 reference statements)
0
8
0
Order By: Relevance
“…Prior studies identified oligodendrocytes as possible targets of developmental and adult TCDD toxicity in the hippocampus, cerebellum, and medulla oblongata ( Fernández et al, 2010 ; Rosińczuk et al, 2015 ; Gileadi et al, 2021 ). These studies were limited to gene expression data from homogenized tissues and analysis of histological sectioning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies identified oligodendrocytes as possible targets of developmental and adult TCDD toxicity in the hippocampus, cerebellum, and medulla oblongata ( Fernández et al, 2010 ; Rosińczuk et al, 2015 ; Gileadi et al, 2021 ). These studies were limited to gene expression data from homogenized tissues and analysis of histological sectioning.…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies examining the adverse effects of contaminant-induced AHR activation on brain health have been corroborated by laboratory investigations using animal models to understand the impact of AHR agonist exposure on brain development and behavior. Studies in multiple model organisms have demonstrated that developmental exposure to AHR agonists produces functional changes in the nervous system ( Dubovický et al, 2008 ; Chen et al, 2012 ; Knecht et al, 2017 ; Gileadi et al, 2021 ; Holloway et al, 2021 ). In rats, exposure to the AHR agonist benzo[a]pyrene (BaP) during critical postnatal periods of development resulted in impaired learning and memory with deficiencies being persistent and exacerbated with age ( Chen et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prenatal and postnatal exposure can cause neurodevelopmental delay and cognitive impairment in children (Ames et al, 2019). Gileadi et al (2021) explored the effect of TCDD exposure during pregnancy on brain structure in mouse offspring. MRI of the offspring exposed to TCDD during pregnancy revealed that the volume of ventral hippocampus, hypothalamus, cerebellum, and other brain regions were increased, while the crus I and papillary bodies of the cerebellar hemisphere were decreased.…”
Section: Autism Mouse Models Related To Environmental Exposures Durin...mentioning
confidence: 99%
“…We found that opposing effects were associated with high dioxin levels, observing both volume increases and volume decreases. Previous animal studies suggested that the effects of persistent organic pollutants (POPs), including dioxins, might be nonmonotonic: POPs exert both promoting and suppressing effects on neuronal dendritic growth, depending on their dose and the brain region, which may lead to brain volume increases and decreases, respectively [22][23][24].…”
Section: Regional Brain Volume Changes Associated With Blood Dioxin L...mentioning
confidence: 99%